PROSPEK PENGEMBANGAN USAHA TERNAK KAMBING DI DESA TULABOLO BARAT - Siskawati S Ali; Mahludin H Baruwadi; St Aisyah Ramli (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
The goat-farming business has quite promising prospects for development. This research aims to analyze the prospects for developing goat farming businesses in West Tulabolo Village, East Suwawa District. Using snowball sampling techniques, six breeders, two village officials, and one extension officer were selected as informants for this study. This research uses primary and secondary data sources. Research data was analyzed using the SWOT analysis framework (strengths, weaknesses, opportunities, and threats). Based on the research results, it show that the IFE (internal factor evaluation) matrix score is 3,27 and the EFE (external factor evaluation) matrix score is 3,04. This shows that the prospects for developing the goat farming business in West Tulabolo Village are strong (3,0–4,0) in square one, consisting of market development and market penetration. Market development is done by improving the quality of breeder resources, and promoting and increasing public knowledge to encourage participation in goat production. Apart from that, it is important to implement a market penetration strategy to increase the market share of the goat farming business. Thus, we hope that establishing a goat farming business will provide a profitable opportunity for both breeders and the community in West Tulabolo Village.